Prove that $\sin 2 x+2 \sin 4 x+\sin 6 x=4 \cos ^{2} x \sin 4 x$
$L.H.S.$ $=\sin 2 x+2 \sin 4 x+\sin 6 x$
$=[\sin 2 x+\sin 6 x]+2 \sin 4 x$
$=\left[2 \sin \left(\frac{2 x+6 x}{2}\right) \cos \left(\frac{2 x-6 x}{2}\right)\right]+2 \sin 4 x$
$\left[\because \sin A+\sin B=2 \sin \left(\frac{A+B}{2}\right) \cos \left(\frac{A-B}{2}\right)\right]$
$=2 \sin 4 x \cos (-2 x)+2 \sin 4 x$
$=2 \sin 4 x \cos 2 x+2 \sin 4 x$
$=2 \sin 4 x(\cos 2 x+1)$
$=2 \sin 4 x\left(2 \cos ^{2} x-1+1\right)$
$=2 \sin 4 x\left(2 \cos ^{2} x\right)$
$=4 \cos ^{2} x \sin 4 x$
$=R.H .S.$
Prove that $\frac{\cos 4 x+\cos 3 x+\cos 2 x}{\sin 4 x+\sin 3 x+\sin 2 x}=\cot 3 x$
The value of $ \cos ^{3}\left(\frac{\pi}{8}\right) \cdot \cos \left(\frac{3 \pi}{8}\right)+\sin ^{3}\left(\frac{\pi}{8}\right) \cdot \sin \left(\frac{3 \pi}{8}\right)$ is
$\frac{1}{{\tan 3A - \tan A}} - \frac{1}{{\cot 3A - \cot A}} = $
If $\tan A = \frac{1}{2},$ then $\tan 3A = $
If $\cos \,(\theta - \alpha ) = a,\,\,\sin \,(\theta - \beta ) = b,\,\,$then ${\cos ^2}(\alpha - \beta ) + 2ab\,\sin \,(\alpha - \beta )$ is equal to